Community Economic Empowerment Through Processing Water Hyacinth Into A Variety Of Crafts In An Effort To Support The Save Maninjau Program: Pemberdayaan Ekonomi Masyarakat Melalui Pengolahan Eceng Gondok Menjadi Aneka Kerajinan Dalam Upaya Mendukung Program Save Maninjau - Armiati*, Armiati; Rahmidani, Rose; Irawan, Indra; Susanti, Dessi; Arita, Sri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to: 1) Provide training on how to produce water hyacinth into various kinds of craft products; 2) Provide training on digital marketing; and 3) Provide training on financial management. The series of training activities took place from August to October 2023. This activity began with an initial coordination meeting to prepare for the implementation of PKM activities with Partners in August 2023, followed by the implementation of training. The partners for this activity are the Sadama Group and the Aua Sarumpun Group with a total of 20 participants. The method used is community development through lectures, discussions, questions and answers, practice and mentoring to provide knowledge and skills in craft making, understanding of digital marketing and financial management. Partners also received assistance from water hyacinth drying machines, press machines and sewing machines. Apart from that, partners also created packaging designs, logo and Instagram designs. The results of this service are important for participants to be able to improve product quality and marketing and financial management of partners.